La imagen del inmigrante en la novela española actual (Altre Modernità, 2009)
The latest generation Spanish writers portray in their novels the country's new context of the socio-cultural reality as a consequence of the great migration flow that affected Spain abruptly in the 1990's and that still keeps increasing progressively. This article intends to analyze the immigration phenomenon in the present Spanish fiction as well as the image of the immigrant in the literary world taking into consideration different point of views: the reason for travelling, the legal and working situation, the encounter and the conflict with the customs and the shattered hopes.